Clinical characteristics of Citrobacter meningitis in adults: High incidence in patients with a postneurosurgical state and strains not susceptible to third-generation cephalosporins. (August 2018) - Lien, Chia-Yi; Lee, Jun-Jun; Chien, Chun-Chih; Huang, Chi-Ren; Lu, Cheng-Hsien; Chang, Wen-Neng
Highlights: Citrobacter ( C .) infection in adult bacterial meningitis (ABM) is rarely reported. The clinical characteristics of 14 Citrobacter ABM patients were analyzed. C. koseri was the most commonly implicated Citrobacter strain (57.1%, 8/14). A high incidence (78.6%) in patients with a postneurosurgical state was noted. A high incidence of 3rd-generation cephalosporin nonsusceptible strains was noted. Abstract: Adult bacterial meningitis (ABM) caused by Citrobacter ( C .) infection is very uncommon and the clinical characteristics of this specific infectious syndrome have not been analyzed in the literature. The clinical characteristics of six Citrobacter ABM patients collected during a study period of 30 years (1986–2015) were enrolled, and they accounted for 1.1% (6/540) of our ABM patients. In this study, a total of 14 patients with Citrobacter ABM (six collected from our hospital and eight from the literature) were included for analysis. The 14 patients were nine men, three women and two with unknown gender, aged 31–84 years (median: 64 years), of whom 78.6% (11/14) had an underlying postneurosurgical condition and 21.4% (3/14) belonged to mixed infections. The most common clinical manifestations were fever (50%, 7/14), altered consciousness (50%, 7/14), and headache (28.6%, 4/14). These clinical presentations were neither specific nor unique; therefore, cerebrospinal fluid studies including cultures were important for the diagnostic confirmation. Of the implicated Citrobacter strains, C, koseri was the most common (57.1%, 8/14), followed by C. freundii (21.4%, 3/14) and C. farmeri (7.1%, 1/14). Of the Citrobacter strains collected from CSF specimens of our six Citrobacter ABM patients, 33.3% (2/6) and 66.7% (4/6) were not susceptible to ceftazidime or ceftriaxone, respectively, but they were all susceptible to carbapenem. The therapeutic results showed a mortality rate of 21.4% (3/14).